2021
DOI: 10.1001/jamanetworkopen.2021.22260
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence Police Reporting and Resources During the 2020 COVID-19 Stay-at-Home Order in Chicago, Illinois

Abstract: Key Points Question Are there associations between the COVID-19 stay-at-home order issued March 2020 in Chicago, Illinois, and the rate of domestic violence (DV) police reporting and resource availability? Findings In this cohort study of 77 Chicago community areas, the stay-at-home order was associated with a decrease in the rate of DV police reports by 21.8 crimes per 100 000 persons per month relative to the same months in 2019, a finding observed largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
0
13
1
3
Order By: Relevance
“…For example, one study examining domestic violence calls placed in Chicago during the pandemic found a decrease in calls placed by Black communities but not white communities. Additionally, this study found that communities with less access to resources, generally, were less likely to access domestic violence resources during COVID-19 (Baidoo et al, 2021). Further work should explore the associations between individual-level factors, such as race and ethnicity; socioeconomic status; and geographic location (i.e., living in a rural, urban, or semi-urban), and COVID-19 experiences.…”
Section: Np103mentioning
confidence: 74%
See 1 more Smart Citation
“…For example, one study examining domestic violence calls placed in Chicago during the pandemic found a decrease in calls placed by Black communities but not white communities. Additionally, this study found that communities with less access to resources, generally, were less likely to access domestic violence resources during COVID-19 (Baidoo et al, 2021). Further work should explore the associations between individual-level factors, such as race and ethnicity; socioeconomic status; and geographic location (i.e., living in a rural, urban, or semi-urban), and COVID-19 experiences.…”
Section: Np103mentioning
confidence: 74%
“…Survivors attempting to leave abusive homes faced limited options. For example, informal networks (family and friends) were less accessible or approachable given social distancing recommendations, and options such as shelters may have been perceived as untenable given the risk of contracting COVID-19 ( Baidoo et al, 2021 ). Further, consistent with prior research finding that child welfare agencies were unprepared for large-scale emergencies ( Berne, 2009 ; Daughtery & Blome, 2009 ), many interpersonal violence (IPV) organizations and SASPs felt ill-equipped to adapt and continue services during the pandemic ( Wood et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Включение гендерного анализа в клинико-психологические исследования весьма важно, что иллюстрируется на примере ряда работ, например в работе Keynejad и соавт. [7], где в качестве модели лечения фигурирует именно опыт внутрисемейного насилия, переживаемый женщинами с психическими расстройствами.…”
Section: гендерно обусловленное насилие и его распространенностьunclassified
“…Полагают, что данные о насилии повсеместно занижаются; исследования выявляют более высокий процент женщин, подвергающихся насилию, чем об этом свидетельствуют соответствующие национальные оценки распространенности [7]. Женщины с симптомами психического неблагополучия, как правило, чаще становятся жертвами насилия, как правило, чаще, чем женское население страны в целом [10].…”
Section: гендерно обусловленное насилие и его распространенностьunclassified
See 1 more Smart Citation